The erosionally confined to emergent transition in a slope‐derived blocky mass‐transport deposit interacting with a turbidite substrate, Ventimiglia Flysch Formation (Grès d'Annot System, north‐west Italy). Issue 4 (10th February 2022) - Marini, Mattia; Patacci, Marco; Felletti, Fabrizio; Decarlis, Alessandro; McCaffrey, William
Abstract: Basal interaction beneath frontally‐emergent mass‐transport deposits has been widely documented in seismic data, but its effect on deposit heterogeneity not convincingly calibrated at outcrop. Several blocky mass‐transport deposits occur as part of the Late Eocene Ventimiglia Flysch of north‐west Italy, comprising slope‐derived marlstones, representing the original slide, and turbidite material, entrained after erosion of substrate sediments; this study reports on the best exposed. Correlation of twenty‐nine sedimentary logs tied to the hosting turbidite stratigraphy allows thickness and facies changes to be tracked over an area of ca 40 km 2, spanning the erosionally confined to emergent transition. A basal erosion >55 m deep and several kilometres wide confines a marlstone megabreccia containing megaclasts of up to 1 km across, interpreted as the product of a submarine slide originated from a sector collapse of the western basinal slope. Approaching the downstream limit of this erosional confinement the marlstone megabreccia is replaced by highly deformed turbidites that, more distally, are in turn superseded by a debrite composed dominantly of turbidite material. Structural and textural characteristics suggest that the distally‐extending debrite was deposited by a forerunner debris flow formed as substrate sediments liquefied ahead of the advancing slide, whereas the deformed turbidites were accumulated at slide margins shortly before it came to a halt. Farther downstream, the debrite is a few metres thick and sits onto the undisturbed basin floor, indicating that the mass flow became emergent distally, and was sufficiently mobile (with an estimated runout in excess of a few tens of kilometres) to redistribute the material evacuated from the basal erosion (>0.5 km 3 ). The mass‐transport deposit terminates upward into a graded marlstone conglomerate deposited by a late‐stage multiphase flow. This study provides a rare insight into facies variation in a frontally‐emergent mass‐transport deposit, showing how basal interaction with poorly consolidated substrates can result in erosional confinement and significant transformation of the parental flow.